(untitled) (World Bulletin of Public Health, 2025)
Impaired placentation is an important contributing factor to intra-uterine growth restriction and pre-eclampsia in fetuses with congenital heart defects (CHD). These pregnancy complications occur more frequently in pregnancies with fetal CHD. One of the most important factors influencing the life of children with CHD is neurodevelopmental delay, which seems to start already in utero.Gestational diabetes mellitus (GDM) and preeclampsia (PE) are common pregnancy complications with similar risk factors. Although GDM is associated with PE, the exact mechanism underlying the association is unclear